COLLABORATIVE GOVERNANCE DALAM LAYANAN BUS RAPID TRANSIT DI KOTA SURAKARTA TAHUN 2010-2019: STUDI TENTANG KEGAGALAN KOLABORASI - Fitriyani, Elisa; Suharto, Didik Gunawan (UNIVERSITAS MUHAMMADIYAH MATARAM, 2021)
This research aims to analyze the success and the effectiveness of collaborative governance process in bus rapid transit service in Surakarta City. The object of research is collaborative process in bus rapid transit service in Surakarta City in 2010-2019. This research was conducted through descriptive qualitative approach. Techniques of collecting data used were in-depth interview and documentation source deriving from relevant document. Informant of research consisted of related stakeholder: Surakarta City Transportation Service Office, Transportation Technical Implementing Unit (TIU) of Surakarta City, Perum DAMRI Surakarta, and PT. Bengawan Solo Trans. Technique of analyzing data used was an interactive model of analysis. The result of research shows firstly that face to face process is a preliminary step in establishing cooperation through direct dialog between stakeholder. Trust building process has been conducted since face-to-face dialogue aiming to keep the collaboration running well. Commitment to process is displayed in the form of Memorandum of Understanding (MoU) document and consortium establishment, PT. Bengawan Solo Trans. Shared understanding effort is implemented in the form of both formal and non-formal routine meeting. Collaborative process loses its momentum in intermediate outcome phase due to the loss suffered from by Perum DAMRI, thereby affecting the good cycle incentive in building trust and commitment. Secondly, in relation to successful collaboration, network structure has been created formally and there are written agreement and contract. The commitment to a common purpose wanes gradually ending up in cooperation contract termination. Trust among the participant also wanes due to stakeholders’ non-performance. Governance, access to authority, distributive accountability/responsibility, and information sharing has been stated formally in Memorandum of Understanding and has run normatively. In the aspect of access to resources, collaborative process fails along with the unavailable financial resource to subsidize bus rapid transit service. Collaborative governance process in bus rapid transit service needs the available access to adequate resource.